Smart Homes: Undeniable Reality or Always Just around the Corner? - Brush, A.J.; Hazas, Mike; Albrecht, Jeannie (IEEE Pervasive Computing, 2018)
With inexpensive wireless devices that don't require a home remodel, maturing standards, mobile devices for remote access, and the emergence of speech appliances as a user interface for in-home interaction, it's an exciting time for smart homes around the world.